European mutual funds (Park Ridge, N.J. ; London, England : Noyes Data Corporation, 1973)
This book examines the growth of the European mutual fund industry. It analyses the extent of the effects of the recent legislation on Foreign Mutual Funds operating in Switzerland as well as other European countries.
usc 21/09/2017
Loans
Keywords: Mutual funds; Europe